2007
DOI: 10.1007/s11745-007-3136-3
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Proteins that Bind Polyunsaturated Fatty Acids: Demonstration Using Arachidonic Acid and Eicosanoids

Abstract: Polyunsaturated fatty acids (PUFA) and their biological derivatives, including the eicosanoids, have numerous roles in physiology and pathology. Although some eicosanoids are known to act through receptors, the molecular actions of many PUFA remain obscure. As the three-dimensional structure of eicosanoids allows them to specifically bind and activate their receptors, we hypothesized that the same structure would allow other proteins to associate with PUFA and eicosanoids. Here, we demonstrate that biotinylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The association with vesicles might provide a regulated source of GTP for GTPases that control intracellular trafficking, while the potential interaction with integrin cytoplasmic domain-associated protein 1α (ICAP-1α) as a consequence of Rac activation might affect cell morphology and behavior during adhesion [61]. NDK-B further binds polyunsaturated fatty acids [62], interacts with heterotrimeric G protein βγ dimers [63], facilitates coat protein complex II assembly [64], and induces c-myc [65] in various cell types. These functions of NDK-B could, if present in adipocytes, provide additional mechanisms by which NDK-B nitration might alter adipocyte biology.…”
Section: Discussionmentioning
confidence: 99%
“…The association with vesicles might provide a regulated source of GTP for GTPases that control intracellular trafficking, while the potential interaction with integrin cytoplasmic domain-associated protein 1α (ICAP-1α) as a consequence of Rac activation might affect cell morphology and behavior during adhesion [61]. NDK-B further binds polyunsaturated fatty acids [62], interacts with heterotrimeric G protein βγ dimers [63], facilitates coat protein complex II assembly [64], and induces c-myc [65] in various cell types. These functions of NDK-B could, if present in adipocytes, provide additional mechanisms by which NDK-B nitration might alter adipocyte biology.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking global LOX activity, even at normal temperatures, greatly decreases extracellular ROS production and has no effect on intracellular superoxide formation in diaphragm muscle in heat exposure (65). Recent evidence suggests that HETEs, leukotrienes, AA, and other eicosanoid products can directly bind and interact with numerous intracellular proteins, including cytoskeleton components associated with the contractile machinery (10). Such lipid-protein interactions are believed to be important in normal regulatory processes of the cell, such as water balance across the cell membrane (44) and GLUT4 translocation to the muscle cell membrane (56).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we and others showed that several polyunsaturated fatty acids (PUFAs) have selective cytotoxic action on many tumor cells of different types with little or no action on normal cells [1] – [14] . But, PUFAs themselves are not very effective in eliminating cancer cells in an in vivo situation partly, due to the fact that they are tightly bound to albumin and other proteins and hence, are unavailable to bring about their tumoricidal action [15] – [17] . Furthermore, PUFAs may be metabolized into several eicosanoids that may have other unwanted actions.…”
Section: Introductionmentioning
confidence: 99%